(untitled) (Signifiances (Signifying), 2019)
In the line of the academic presentation of Saussure’s « Cours de linguistique générale » that, for long, prevailed over the master’s authentic writings that were only published much later, the linguistic sign came to be represented as a two-headed entity with two inseparable yet distinct facets. Today, however, the question remains whether their relationship is one of (symbolic) concordance or (diabolic) conflict. Whether it is considered or not as authentic data, the signified of the linguistic unit stands out as the more evanescent of the two components. Although widely referred to when reflecting on language, the notion of a unitary signified is therefore a much debated issue today, and the topic of the present paper. Indeed, with its inherent dualistic nature and the ontological perspective it implies, it raises as many drawbacks as benefits. Key-words : linguistic unit ; semiotic triangle ; the signified and its accessibility